Implementation of Human Robot Interaction on UDOO Board - Min Raj Nepali; Priyanka C Karthik; Jharna Majumdar (Institute of Advanced Engineering and Science, 2016)
Advanced Robot for Interactive Application (ARIA) is a Humanoid Robotic Head which is capable of mimicking Various Human Facial Expressions. Much work has been done on Implementation of Humanoid Robotic Head with High end systems and Personal Computers (PCs). This paper presents the essential elements necessary for the implementation of Advanced Robot for Interactive Application (ARIA) on UDOO Board. The main aim of the Project was to develop a control system and Graphical User Interface (GUI) for ARIA to deliver real time human facial expressions using embedded board. Humanoid Robotic Head which is capable of mimicking Human Facial Expressions in Real time. Implementation of ARIA involved careful selection of Embedded Board, actuators, control algorithms, motor drivers, operating system, communication protocols, and programming languages. The Board contains a Quad Core A9 Processor and a Controller embedded on it, which are interconnected. In this project the controller is dedicated to control micro servo motors which are controlling eyes, eyebrows and eyelids movements whereas the Processor Handles the Dynamixel motors, GUI and different communication modules.